La etnobotánica al servicio de las comunidades - Aparicio, Gustavo; Ladio, Ana; Hilger, Norma; Pochettino, María Lelia; Vignale, Nilda Dora; Suárez, María Eugenia (Revista Aves Argentinas, 2020)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).